Roadmap for implementing environmental DNA (eDNA) and other molecular monitoring methods in Finland–Vision and action plan for 2022–2025 - Norros, Veera; Laamanen, Tiina; Meissner, Kristian; Iso-Touru, Terhi; Kahilainen, Aapo; Lehtinen, Sirpa; Lohtander-Buckbee, Katileena; Nygård, Henrik; Pennanen, Taina; Ruohonen-Lehto, Marja; Sirkiä, Päivi; Suikkanen, Sanna; et al. (Finnish Environment Institute, 2022)
Technological development in molecular methodology has been extremely fast in the past two decades, and groundbreaking new approaches have been introduced. It is now possible to detect and quantify DNA or RNA of target species or even map the whole species community in environmental samples of water, sediment, soil, air or assemblages of whole organisms. Moreover, the costs of high-throughput sequencing and other advanced molecular methods have decreased and methodological pipelines from sampling to data analysis developed sufficiently to allow large-scale, routine application of the new methods in environmental monitoring. This presents a huge opportunity to improve the coverage, accuracy and cost-efficiency of monitoring, enabling a much more complete picture of biodiversity and the state of the environment and their trends. As the new European Biodiversity Strategy for 2030 and other international policies to halt biodiversity loss and the degradation of habitats are translated into concrete measures, the quality of the monitoring data will play a crucial role in determining their success or failure. In this roadmap commissioned by the Finnish Ministry of the Environment, we assess the state-ofthe-art in molecular monitoring methods in Finland within the international context, identify challenges and development areas that remain to be addressed and propose an action plan for promoting the coordinated implementation of molecular methods in national monitoring programs. Apart from the most recent scientific literature, our analysis is based on survey results, direct enquiries and interviews. Participation of the national community of experts from different sectors was enabled and invited at several stages of the roadmap preparation. Internationally, molecular monitoring methods are being actively developed and are routinely implemented in monitoring across different taxa and ecosystems. In Finland, molecular monitoring methods have been tested and piloted by all major institutions responsible for environmental monitoring, and the methods are already applied routinely in the monitoring of individual game species such as the wolf and European and Canadian beaver. However, other areas such as the monitoring of biodiversity, threatened species, non-mammalian invasive species or emerging plant or animal pests remain less developed, and national efforts and expertise are scattered across different organizations. Funding and know-how are perceived as the most important factors limiting molecular monitoring method implementation. We estimate that extensive, routine implementation of a wide range of molecular monitoring methods is conceivable in Finland before 2030. As the primary development areas for reaching this goal, we identify (i) international coordination and standard development, (ii) networking across sectors, (iii) education, (iv) infrastructure, (v) reference sequence libraries and the mapping of whole genomes, and (vi) modelling and analysis tool development. For concrete actions in 2022–2025, we propose (1) a cross-governmental funding instrument, (2) a permanent working group responsible for national and international coordination, (3) a national network and (4) an online platform to enhance interaction and knowledge transfer, as well as (5) a national data management system with collectively agreed data and metadata formats and standards.
Keywords: biodiversity; environmental monitoring; metabarcoding; next-generation sequencing; monitoring strategy